Strategi Pemasaran Keripik Tempe Pada Situasi Pandemi Covid-19 (Studi Kasus Home Industry Nikmat Sari Kecamatan Kramatwatu Kabupaten Serang Provinsi Banten) - Vera Maria; Firli Agusetiawan Shavab (Tirtayasa Ekonomika, 2021)
Since the beginning of 2020, the world is being hit by the Coronavirus (Covid 19) pandemic. The Government of Indonesia created and endorsed a policy to break the chain of spread of Covid 19 by imposing a large-scale social restriction (PSBB) policy. The PSBB policy further restricts the movement and activities of the community that slows economic activity. In fact, before the Covid 19 pandemic, tempeh chips products produced by The Delicious Sari home industry in the process of growing. This condition will certainly make the development of the home industry Nikmat Sari located in The District Kramatwatu Serang Banten Province becomes hampered even has a tendency to soon experience a gradual bankruptcy phase. This should begin to be observed and handled more seriously by the home industry Nikmat Sari if it wants to be able to survive and compete in the business world today by redesigning its marketing strategy. Therefore, the home industry of Nikmat Sari should start as soon as possible to vaccinate internal factors and external factors that they have in order to design an effective marketing strategy in attracting consumers' buying interest in tempeh chips products Nikmat Sari. One analysis that can be used to design marketing strategies using SWOT analysis